Nanotechnology in Cancer Drug Delivery and Selective Targeting. (16th January 2014) - Sutradhar, Kumar Bishwajit; Amin, Md. Lutful
Abstract : Nanoparticles are rapidly being developed and trialed to overcome several limitations of traditional drug delivery systems and are coming up as a distinct therapeutics for cancer treatment. Conventional chemotherapeutics possess some serious side effects including damage of the immune system and other organs with rapidly proliferating cells due to nonspecific targeting, lack of solubility, and inability to enter the core of the tumors resulting in impaired treatment with reduced dose and with low survival rate. Nanotechnology has provided the opportunity to get direct access of the cancerous cells selectively with increased drug localization and cellular uptake. Nanoparticles can be programmed for recognizing the cancerous cells and giving selective and accurate drug delivery avoiding interaction with the healthy cells. This review focuses on cell recognizing ability of nanoparticles by various strategies having unique identifying properties that distinguish them from previous anticancer therapies. It also discusses specific drug delivery by nanoparticles inside the cells illustrating many successful researches and how nanoparticles remove the side effects of conventional therapies with tailored cancer treatment.